Review of Irritable Bowel Syndrome Treatment - M.R Ghadir (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2012)
Background and Objectives: Irritable bowel syndrome is one of the most common functional gastrointestinal disorders striking 10-20% of the world population. Although most patients do not take medical assistance, this disease enforces significant cost on the patient and health systems and has negative effects on quality of life of the individual. After diagnosis ,treatment of this disease is the next step. Many pathways of treatment has been introduced and the efficacy of each other has been established in one way or another. The first step in the path of treatment is education and confidence of patients that might also be the most important step. Fiber diet, probiotic, anti-cholinergic and anti antispasmodics, laxatives, anti-diarrhea, the drugs affecting serotonin receptors, antidepressants and anti-anxiety, the chloride channel activator and non-drug methods such as cognitive-behavior therapy, hypnotherapy, acupuncture and herbal medicine each of which has been tested on irritable bowel syndrome and efficacy of each one has been indicated in one way or another. This paper tried to outline new treatments available in addition to categorization and discussion of various treatments for irritable bowel syndrome.